Fundamentos conceptuales en torno al área de la administración deportiva (2013)
ABSTRACT: Research Group of Applied Science in Physical Activity and Sport GRICAFDE, of the University of Antioquia, and Research Group of Education Interdisciplinary Studies ESINED of the University of San Buenaventura have generated the relevant traceability to enhance the sports administration area throughout the training cycle offered by the two universities. Thus, after the formal major, postgraduate studies, research process, extension, social projects and continued education from seminars, associate degrees and conferences in several academic events. These stages generate positive ties to show and to impact the educative management in educative institutions. One element that allows developing such actions, it is a research developed between the two universities and from which initial conceptual agreements are reached, always from the perspective of continuous improvement and will be the starting point in generating community from the academic disciplinary knowledge based on research processes and uses knowledge of sports administration and sports management. Determining their relationship to education, so the subject can be part of the Educational Institution and the Sports Community Organization as a historical construction, individual, social and contextual.